A Modified Tumor-Node-Metastasis Classification for Primary Operable Colorectal Cancer. Issue 1 (16th October 2020) - Zhang, Chundong; Mei, Zubing; Pei, Junpeng; Abe, Masanobu; Zeng, Xiantao; Huang, Qiao; Nishiyama, Kazuhiro; Akimoto, Naohiko; Haruki, Koichiro; Nan, Hongmei; Meyerhardt, Jeffrey A; Zhang, Rui; et al.
Abstract: Background: The American Joint Committee on Cancer (AJCC) 8th tumor-node-metastasis (TNM) classification for colorectal cancer (CRC) has limited ability to predict prognosis. Methods: We included 45 379 eligible stage I-III CRC patients from the Surveillance, Epidemiology, and End Results Program. Patients were randomly assigned individually to a training (n = 31 772) or an internal validation cohort (n = 13 607). External validation was performed in 10 902 additional patients. Patients were divided according to T and N stage permutations. Survival analyses were conducted by a Cox proportional hazard model and Kaplan-Meier analysis, with T1N0 as the reference. Area under receiver operating characteristic curve and Akaike information criteria were applied for prognostic discrimination and model fitting, respectively. Clinical benefits were further assessed by decision curve analyses. Results: We created a modified TNM (mTNM) classification: stages I (T1-2N0-1a); IIA (T1N1b, T2N1b, T3N0); IIB (T1-2N2a-2b, T3N1a-1b, T4aN0); IIC (T3N2a, T4aN1a-2a, T4bN0); IIIA (T3N2b, T4bN1a); IIIB (T4aN2b, T4bN1b); and IIIC (T4bN2a-2b). In the internal validation cohort, compared with the AJCC 8th TNM classification, the mTNM classification showed superior prognostic discrimination (area under receiver operating characteristic curve = 0.675 vs 0.667, respectively; 2-sided P < .001) and better model fitting (Akaike information criteria = 70 937 vs 71 238, respectively). Similar findings were obtained in the external validation cohort. Decision curve analyses revealed that the mTNM had superior net benefits over the AJCC 8th TNM classification in the internal and external validation cohorts. Conclusions: The mTNM classification provides better prognostic discrimination than AJCC 8th TNM classification, with good applicability in various populations and settings, to help better stratify stage I-III CRC patients into prognostic groups.